Minority Rights and Majority Interests: an Analysis of Development-Induced Displacement in the Narmada Valley, India - Buelles, Anni-Claudine (Université d'Ottawa / University of Ottawa, 2012)
This thesis analyzes how the interests of minority and majority groups in state-led development practices can be bridged, with the Indian tribals affected by the Sardar Sarovar Dam Project (SSP) serving as a context for my analysis. The SSP threatens the livelihoods of approximately 100,000 people with displacement, who are primarily comprised of Indian tribal minorities. The construction of the SSP makes tribals more vulnerable to the risks associated with development-induced displacement, such as landlessness, joblessness, homelessness, marginalization, and food insecurity. When analyzing the SSP, a lack of adequate compensation, resettlement, and legal protection for the tribals becomes apparent. This has led to discussions of human rights violations among the national and international community, raising concerns regarding the protection of minority groups affected by state-led development. Attention is placed on what it means to be a citizen of a country in terms of legal representation and state protection, and how the under-representation of societal groups can lead to the creation of second-class citizens. The objective is to go beyond current discussions of human rights neglect in the context of the SSP by analyzing the position of minority rights in state-led development practices.
Keywords: development-induced displacement; minority rights; Sardar Sarovar Dam; internally displaced people; indigenous people; majority interest; state-led development; displacement; capability approach; Narmada Bachao Andolan; minority rights in India